Cases in comparative politics - O'Neil, Patrick H. (W.W. Norton & Company, 2010)
Cases in Comparative Politics, Third Edition, is a set of thirteen country studies that describe politics in the United Kingdom, the United States, France, Germany, Japan, Russia, China, India, Iran, Brazil, Mexico, South Africa, and Nigeria. This casebook applies the conceptual framework developed in the text across countries with a consistent organization that facilitates comparison and aids understanding.